PENGARUH PROBLEM BASED LEARNING BERBANTUAN SPICO (SPINNER GAME ECONOMY) TERHADAP HASIL BELAJAR SISWA SMA - Jusriadi Amri; Muhammad Yany; Syamsuria Syamsuria; Nia Febrianti; Nurul Atika; Mardian Syah (STKIP Persada Khatulistiwa Sintang, 2025)
This research was conducted due to the low problem-solving skills and learning outcomes of students at SMA Negeri 13 Bone due to unattractive conventional learning methods and the minimal use of interactive learning media. This study aimed to determine the effect of implementing the Problem-Based Learning model supported by SPICO (Spinner Game Economy) learning media on student learning outcomes at SMA Negeri 13 Bone. This study was a pre-experimental study with a One Group Pre-Test and Post-Test design. A sample of 35 students was selected using a random sampling technique. Data were collected through learning achievement tests and documentation, then analyzed using descriptive and inferential statistics, including normality tests, homogeneity tests, and paired sample tests. The results showed a significant increase, from an average pre-test score of 39.86 to a post-test score of 85.43, with the majority of students in the high to very high categories. These findings indicate that the implementation of PBL supported by SPICO media has an impact on student learning outcomes at SMA Negeri 13 Bone and encourages students to be more active, critical, and confident in their learning.